Islam Nusantara: Solusi Menyikapi Problem Radikalisme Agama - Kurdi, Alif Jabal; Inayatussahara, Nur Azka (Universitas Islam Negeri Raden Intan Lampung, 2019)
Islam coming to Indonesia is not coming to an empty land, but its people have built up on a strong tradition and culture. As an initiative step, the preachers used the dialectical approach of culture. Nusantara Islam is a religious expression that is in accordance with the local culture of the archipelago, because there is a dialectic between religious texts and local Nusantara culture and traditions. However, Nusantara Islam has been misunderstood by the notion of radicalism, this group does not accept acculturation of culture in religion. So that the negative view of the Nusantara Islam in it accommodates local cultural rituals. So this paper aims to discuss how the dialectics of culture and religion in the context of the spread of Islam as exemplified at the time of the Prophet and in the time of Walisongo. To support the course of this study researchers used a historical analysis approach. As a result of the analysis the researchers found that cultural and religious dialectics had taken place at the time of the Prophet. in the face of the traditions of the people of Mecca, the Prophet did not reject and erase all their long-standing practices. so that what was done by Indonesian preachers is not contradictory in Islam. Thus, this paper is expected to be able to answer the negative responses of puritans who want to purge Islam from all forms of cultural acculturation in it and be able to affirm Nusantara Islam as a characteristic of Indonesian Islam free of radicalism and respect for plurarity.